THE USE OF NEW EDUCATIONAL TECHNOLOGIES IN THE TEACHING OF SPECIAL SCIENCES - Pirnazarov Ilxom Islamovich; Karimov Tashmukhamed Khalmukhamedovich; Gulboyev Sardor Baxtiyor o`g`li (Web of Journals Publishing, 2025)
The use of new pedagogical technologies in the teaching of special disciplines is important to improve the quality of education, arouse the interest of students and the effective organization of the educational process. Below we briefly dwell on the basic data and modern methods used.
Keywords: Pedagogical Technology, Engineering Communications, Boomerang, Adiabatic.